Three new species of Vitaceae from mesoamerica - Lombardi, J. A. (Missouri Botanical Garden, 2005)
Three new species, Cissus nicaraguensis, C. patellicalyx, and Ampelocissus mesoamericana, are described from Nicaragua, Costa Rica, and El Salvador, respectively. Cissus nicaraguensis can be distinguished from all other Neotropical species by the combination of urceolate calyx and simple leaves. Cissus patellicalyx is recognized by its subspherical floral buds, immature fruits minutely tuberculate when dried, and the distinctly raised nerves of the abaxial leaf surface. Ampelocissus mesoamericana is characterized by lenticels, indument, and the obpyriform flower buds.
Keywords: Ampelocissus; Cissus; mesoamerica; Vitaceae